Reishi Protein LZ-8 Induces FOXP3+ Treg Expansion via a CD45-Dependent Signaling Pathway and Alleviates Acute Intestinal Inflammation in Mice. (24th June 2013) - Hsu, Hsien-Yeh; Kuan, Yen-Chou; Lin, Tung-Yi; Tsao, Shu-Ming; Hsu, Jason; Ma, Li-Juan; Sheu, Fuu
Abstract : LZ-8, an immunomodulatory protein isolated from Ganoderma lucidum (also known as Ling-Zhi or Reishi), has been shown to promote cell proliferation and IL-2 production in T cells. In this study, we show that LZ-8 induces the expansion of both murine and human CD4 + T cells into FOXP3 + regulatory T (Treg) cells. LZ-8 treatment was found to stimulate a 4-fold and a 10-fold expansion in the Treg populations of murine and human primary CD4 + T cells, respectively. In addition, the expression of CTLA-4 and IL-10 was induced in LZ-8-treated CD4 + T cells. Using neutralizing antibodies and gene-deficient T-cell lines, we also found that LZ-8 promotes Treg expansion through a CD45-mediated signaling pathway and that the CD18-dependent induction of IL-2 was involved in Treg formation and IL-10 production. The suppressive activity of LZ-8 was confirmed using a murine model of DSS-induced colitis; the disease was alleviated by the adoptive transfer of LZ-8-treated CD4 + T cells. In conclusion, a new regulatory function for LZ-8 was identified, and the molecular mechanisms underlying this function were elucidated.